일반병실을 음압격리병실로 전환 시 병실 전환 방식에 관한 연구 - 국가지정입원치료병상과 긴급치료병상을 중심으로 - 김지윤; 이현진; 권순정 (의료·복지 건축, 2023)
Purpose: The 2015 Middle East Respiratory Syndrome (MERS) outbreak and the recent COVID-19 pandemic have highlighted the lack of negative pressure isolation rooms and the fragility of the healthcare system. The need for healthcare facility transformation for respiratory infectious diseases has become more prominent due to COVID-19, and the purpose of this study is to provide a foundation for the rapid, economical, and safe construction of negative pressure isolation wards. Methods: This study analyzes the current status of hospitals that have been converted to negative pressure isolation rooms, and provides architectural plans and examples to provide a reference for bedroom change. Research data of this study have been obtained by analyzing the drawings of negative pressure isolation wards of nationally designated inpatient treatment beds and urgent isolation beds. In addition, the relevant literature of urgent isolation beds has been analyzed to derive bedroom change type. Result: In this study, a total of 21 isolation bed conversion methods have been presented. Implications: In order to change efficiently from a general ward to an isolation ward, it is necessary to consider the actual hospital's infectious disease transmission patterns and facility conditions.
Keywords: COVID-19; Nationally Designated Isolation Unit; Urgent Isolation Beds; Negative Pressure Isolation Rooms; Conversion Type; 코로나19; 국가지정음압격리병상; 긴급치료격리병상; 음압격리병실; 전환 방식